Migration experience, aspirations and the brain drain theory and empirical evidence - Marcus H. Böhme; Toni Glaser (Kiel Institute for the World Economy (IfW), 2014)
We develop a theoretical model of human skill formation and emigration. Additionally to existing brain drain models, we partly endogenize the heterogeneity of the individuals, by introducing aspirations. Emigration of an individual will result in a migration experience, which increases the migrant's aspirations. This will induce her to invest more in the education of her children back home. We find that this aspirations effect increases the average skill level in the society for a given migration rate. We show that the optimal migration rate that maximizes the post-migration skill-rate of the population is higher if we allow for the aspirations effect of migration. We use panel data from Indonesia to demonstrate that a migration experience has an aspirations increasing effect and calibrate our model accordingly. Our results suggest that there are potentially more countries than previously assumed which benefit from migration.
Keywords: D03; F22; I25; J61; O15; 330; migration; brain gain; aspirations; education